Processi euristici e marketing imprenditoriale - Guercini, Simone (Piccola Impresa / Small Business, 2012)
The article examines the gap between theory and practice of marketing in small and medium-sized enterprises, proposing the thesis that a decisive contribution to understand and overcome it can be derived from the study of heuristics that characterize the behavior of top decision makers. After an analysis of the evolution of the literature on heuristics in cognitive science and especially in experimental psychology, this article examines the increasing attention paid to the heuristics in the study of marketing and strategic management. The article discusses the types of heuristics proposed in the literature, critically compared with two dimensions of heuristics (specificity and convergence) the discussion of which represents an original content of the paper as emerging from a case analysis of an Italian firm of the textile sector.